2022
DOI: 10.1002/jmv.27547
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing of Mycobacterium indicus pranii for the severe form of COVID‐19 patients in India: A cohort study

Abstract: Severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) induces the production of proinflammatory cytokines, which results in a cytokine storm, and immune‐modulators like Mycobacterium indicus pranii (MIP) might ameliorate coronavirus disease of 2019 (COVID‐19) related cytokine storm. Therefore, the present study evaluates whether MIP offers an advantage in the treatment of severe COVID‐19 patients infected with SARS‐CoV‐2. A prospective MIP cohort study was conducted in chest disease hospitals in Srinaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…For above statistical test level of statistical significance was set at P < 0.05. Statistical analysis was performed as per method of [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…For above statistical test level of statistical significance was set at P < 0.05. Statistical analysis was performed as per method of [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…The perplexing etiology of COVID-19 is marked by significantly enhanced cytokine production which results both in considerable mortality and grave disease progression [ 6 ] The increased case fatality of the recent SARS-CoV-2 pandemic is attributed to uncontrolled and dysregulated cytokine production which results from severe Acute Respiratory Distress Syndrome (ARDS) symptoms, which further causes significantly higher mortality rate in these patients [ 7 ]. Studies across the globe have reported that activation of immune cells by various viruses that infect the pulmonary system promotes secretion of a diverse set of cytokines which enhances endothelial-vascular permeability and allows blood cells and fluid to migrate into the alveoli henceforth causing dyspnea and respiratory failure [ [7] , [8] , [9] , [10] , [11] , [12] ]. In addition to SARS-CoV-2 viruses that induce CS include SARS-CoV-1, H1N1 influenza, H5N1 influenza, Ebola infections, and Influenza Band Parainfluenza virus, [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased infiltration of immune cells inside pulmonary parenchyma. Hyper activation of inflammatory pathway, higher levels of Ferritin and C-Reactive Protein [ 17 , 18 , 19 ] 4) Bacteria Induced CS Increased levels of TNF-α, interluekins chemokines and G-CSF, [ 20 , 21 [51,185,190] 5) SARS-CoV-1 Elevated levels of IL-8, IL-1β, TNF-α, and IL-6 in alveolar lavage and blood plasma and significant Lymphopenia, higher levels of Ferritin and C-Reactive Protein [ 8 ,204] 6) MERS-CoV-1 Significantly higher levels of procalcitonin, and IL-6 being a prominent indicator of CS. The main differentiating factors includes absence of hyperferritinemia and absence of any significant elevation in C reactive protein levels [ [ 20 , [18] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ], 202] 7) Macrophage Activation Syndrome Ferritin levels above the threshold level of 10,000 ng/mL.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical disease affects the respiratory system and is characterized by acute respiratory distress syndrome. In addition to pulmonary involvement, SARS-CoV-2 has been isolated from cardiovascular, digestive, neurological and renal tissues [ 4 , 5 , 6 ]. The incidence of renal failure varies from 0.5% to 25% in hospitalized patients in the absence of medical emergencies related to a pandemic [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%